“My Poor Little Blossom! My Flower of Asia!” : Images of gender and China In English-language novels - Cheung, Cally Hiu Tung (Nanyang Technological University, 2022)
This research examines the literary and cultural representations of China with a particular focus on the representation of women and the gendering of China. Analysing gender representations exposes certain hierarchies that are culturally imposed and bounded, and concretises how gendered concepts such as power and categorisation operate in another culture. It also considers the historical accuracy of Western images of China by studying their significance, prevalence, and influence in English-language novels. Whereas most literary studies analyse only a few exceptional texts, the investigation uncovers significant connections concerning the cultural representation of China drawn from a dataset of 8,438 texts across 117 years, marking out patterns and shifts that arise from the fluctuating relationship between China and the West. This method enables the study of traces, rather than nodes, of China across the literary landscape. These traces are written by authors who have little direct experience yet represent and shape broader sociocultural trends. Numbers ostensibly offer exactitude but may lead to reductive conclusions, an increase in complexity, and the erosion of life experiences. While statistics and numbers can, at times, accrue authority and authenticity, the research does not set out to prove these measures, but instead interrogates how these small representations, portrayals, and impressions contribute to a pervasive attitude of China.